2012
DOI: 10.1371/journal.pgen.1002676
|View full text |Cite
|
Sign up to set email alerts
|

LINT, a Novel dL(3)mbt-Containing Complex, Represses Malignant Brain Tumour Signature Genes

Abstract: Mutations in the l(3)mbt tumour suppressor result in overproliferation of Drosophila larval brains. Recently, the derepression of different gene classes in l(3)mbt mutants was shown to be causal for transformation. However, the molecular mechanisms of dL(3)mbt-mediated gene repression are not understood. Here, we identify LINT, the major dL(3)mbt complex of Drosophila. LINT has three core subunits—dL(3)mbt, dCoREST, and dLint-1—and is expressed in cell lines, embryos, and larval brain. Using genome-wide ChIP–S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…2B. These data complement conclusions of Meier et al who reported that siRNA depletion of PrSet7 and concomitant loss of genome-wide H4K20 mono-and dimethyl modifications, had no effect on expression of any of the specific loci they focused on, the repression of which is dependent upon L(3)mbt through dLINT (12). melanogaster.…”
Section: L(3)mbt Localization On Polytene Chromosomes and Correlationsupporting
confidence: 88%
See 3 more Smart Citations
“…2B. These data complement conclusions of Meier et al who reported that siRNA depletion of PrSet7 and concomitant loss of genome-wide H4K20 mono-and dimethyl modifications, had no effect on expression of any of the specific loci they focused on, the repression of which is dependent upon L(3)mbt through dLINT (12). melanogaster.…”
Section: L(3)mbt Localization On Polytene Chromosomes and Correlationsupporting
confidence: 88%
“…a large set, rather than one specific type of methylated histone. For example, methylated H4K20 appears to be dispensable for L(3)mbt-mediated repression of some genes (12), and it is possible that other mono-and dimethylated histones may perform this function at specific loci.…”
Section: What Are the Necessary And Sufficient Components For L(3)mbtmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies in human and Drosophila have identified novel assemblies that combine MBT and CoREST proteins [20][21][22][23] (Table 1). Human SFMBT1 was isolated in a complex with LSD1 and CoREST (SLC complex) and the remaining subunits of known CoREST complexes.…”
Section: Mbt and Corest Proteins In Common Complexesmentioning
confidence: 99%